Implementasi Teologis Frasa “Mengutus” dalam Yohanes 17:18; 20:21 bagi Gereja dari Perspektif Missio Dei - Manurung, Well Therfine Renward; Kiamani, Andris; Eunike, Meichella Yosepha; Ohoitimur, Reynhard Leonard; Ginting, Samuel Sukanta (STT Bala Keselamatan Palu, 2024)
Abstract: The church is a fluid fellowship of believers (liquid church). An organism created by Jesus Christ Himself as a tangible manifestation of Christ in the world to do His work: calling sinners and proclaiming the gospel of God as an expression of God's love to the world. This research is motivated by the lack of research that explains the relationship between sending and missio Dei, as well as the limitation of mission to evangelism and church growth, the lack of attention to the importance of dialogue and engagement with society, and the neglect of the complex social and political context in which mission is carried out. This research uses a qualitative method with an interpretative approach (interpretative design) so as to find the meaning and implementation of the phrase